Lexical grammar theory in the context of pedagogical linguistics: Lexical and grammatical analysis of the word in higher education institutions - A.L. Sharandin (Ученые записки Казанского университета: Серия Гуманитарные науки, 2017)
The paper covers the methodological aspects of interaction between the lexical and grammatical levels, which can be considered as the key problem of teaching the Russian language. In the context of pedagogical linguistics and the author's theory of lexical grammar as a special aspect of the Russian grammar, the lexical and grammatical analysis of the word in the dialectic unity of language and speech has been performed. The obtained results allow to evaluate the integrative knowledge of vocabulary and grammar considering their interrelation, integrity, and systemic character. The degree and nature of scientific knowledge on pedagogical linguistics are related to the development level of students at schools and universities. The lexical and grammatical analysis has been carried out in two directions: 1) with regard to the word form and 2) with regard to the lexeme word. When syntactical forms (derivatives) are involved in the lexical and grammatical analysis, the active forms of studying the Russian grammar can be applied. They are aimed at description of an objective-denotative situation under different conditions of communication. The suggested plan of lexical and grammatical analysis has been applied using particular linguistic data (by segmentation of the verbal lexeme). The results of the application of lexical grammar theory in practice favor the development of a dialectic understanding of the system with regard to language and speech, morphology and syntax, as well as the interaction between vocabulary and grammar as a whole.